Investigating High School Student Misconceptions: A Rasch-Based Three-Level Diagnostic Evaluation of Osmoregulation and Excretion Systems - Ridwan; Sunarto A. Sura; Diki Koerniadi; Lia Zaradiva; Soeharto Soeharto; Najira; Ghurrotul Bariroh; Fadil Muhammad (Emerging Science Journal, 2025)
This study aimed to develop and validate a three-tier multiple-choice diagnostic assessment instrument to identify misconceptions related to osmoregulation and the excretion system among Indonesian high school students. A total of 281 students from West Sumatra and Jambi Province participated in the research. Employing a quantitative approach, the psychometric properties of a 20-item test were analyzed using Rasch modeling. The analysis revealed that the instrument had strong item reliability (0.84), though person reliability was relatively low (0.55), indicating variability in students’ response consistency. Despite this, the test demonstrated high internal consistency, as shown by a Cronbach's Alpha of 0.90. The mean student ability level (-2.37) was significantly lower than the item difficulty level (0.00), suggesting widespread conceptual gaps among participants. All items met the model’s expectations, with average Outfit Mean Square (MNSQ) at 1.02 and Z-Standard at 0.1. The findings highlight the diagnostic tool’s effectiveness in detecting prevalent misconceptions in biology education. This study contributes to the field by offering a structured and psychometrically sound instrument, supporting more targeted instructional strategies to enhance conceptual understanding in science education.